Analisis Klaster Bentuk Lahan Dengan Pendekatan Indeks Moran dan Local Indicators of Spatial Association (LISA) di Kabupaten Gorontalo - Sri Rahmawati Habie (Jurnal Peweka Tadulako, 2026)
Landforms reflect interactions among geological, hydrological, and human processes, influencing a region’s capacity to support socio economic activities. This study analyzes spatial patterns of landforms in Gorontalo Regency and their relationship with population density using Moran’s I and Local Indicators of Spatial Association (LISA). Data include landform maps, administrative boundaries, and 2024 population density. Analyses were conducted globally (Moran’s I), locally (LISA), using the median approach, and Bivariate Moran’s I. Results indicate that landform distribution is relatively random with weak spatial autocorrelation, whereas population density shows contrasting patterns across neighboring areas. Median and bivariate analyses reveal hidden spatial structures and outliers (Low-High, High-Low), reflecting local mismatches between physical terrain and demographic pressure. These findings highlight the importance of adaptive micro-spatial planning and the consideration of additional variables for sustainable regional development.